Development of scallion (Allium fistulosum L.) in substrate and homeopathic solutions of water hyacinth - Palacios, Sthefany dos Santos Maidana; Ribeiro, Joyce Wandela Viana; Mapeli, Nilbe Carla; Cremon, Cassiano; Mapeli, Ana Maria (Comunicata Scientiae, 2024)
<audio class="audio-for-speech"></audio> Scallion (Allium fistulosum) is a widely appreciated condiment in the Brazilian population, with significant economic and nutritional importance. Organic cultivation alternatives for this crop have been sought. From this perspective, this study aimed to evaluate the development of scallion in a substrate produced from the floating aquatic plant known as Water Hyacinth (Eichhornia crassipes), combined with soil or without it, with the application of homeopathic solutions. A completely randomized experimental design was used, with five replicates and six treatments, namely: Pure Water Hyacinth Substrate (SAP); Water Hyacinth Substrate with Homeopathic solution (SA+HA); Soil and Water Hyacinth Substrate (S+SA); Soil and Water Hyacinth Substrate with Homeopathic solution (S+SA+HA); Pure Soil (SP), and Soil with Homeopathic solution (S+HA). The following parameters were evaluated 60 days after planting: plant height in centimeters (AP), shoot diameter in millimeters (DP), and the number of shoots (NP). Analysis of variance revealed that plant height (AP) did not exhibit significant differences between substrates with or without the homeopathic solution. In contrast, substrates containing Water Hyacinth exhibited greater shoot diameter and number of shoots. This study showed that the Water Hyacinth substrate and homeopathic solution had promising results in the production of scallion seedlings when combined with soil.